Rancangan Program Pelayanan Konseling Berbasis Analisis Maladjustment Konseling Realitas - Nike Julia Safari; Rahma Wira Nita; Triyono Triyono (Jurnal Counseling Care, 2021)
ABSTRACT The aims of this study were to 1) describe students' maladjustment based on a reality counseling approach; 2) design a counseling service program based on the analysis of reality counseling maladjustment. The type of this research is descriptive quantitative. The population of this research is all Class VIII Junior High School 12 Padang totaling 334 people. The sampling technique was carried out by proportional random sampling of as many as 77 participants. The technique of collecting research data was through a questionnaire and the data were analyzed by descriptive statistics of the percentage technique. The results showed that: 1) maladjustment of students based on the reality counseling approach was in a low category; 2) the planned counseling program is basic services in the form of information services. Meanwhile, efforts to overcome maladjustment behavior through group guidance services. Keywords: Program, Counseling Reality, Maladjustment   ABSTRAKTujuan Penelitian ini adalah untuk: 1) mendeskripsikan maladjustment peserta didik berbasis pendekatan konseling realitas; 2) merancang program pelayanan konseling berdasarkan analisis maladjustment konseling realitas. Jenis penelitian ini adalah deskriptif kuantitatif.Populasi penelitian ini adalah seluruh Kelas VIII Sekolah Menengah Pertama Negeri 12 Padang berjumlah 334 orang. Teknik pengambilan sampel dilakukan dengan propotional random sampling yaitu sebanyak 77 partisipan. Teknik pengumpulan data penelitian melalui angket dan data dianalisis dengan statistik deskriptif teknik persentase. Hasil penelitian menunjukan bahwa: 1) Maladjustment peserta didik berbasis pendekatan konseling realitas berada pada kategori sedikit; 2) program konseling yang direncanakan adalah layan dasar dengan bentuk layanan informasi. Sedangkan upaya untuk mengatasi perilaku maladjusmet melalui layanan layanan bimbingan kelompok. Kata Kunci :  Program, konseling Realitas, Maladjustment.